2004
DOI: 10.1529/biophysj.104.043299
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Model of the Human Left-Ventricular Epicardial Myocyte

Abstract: A computational model of the human left-ventricular epicardial myocyte is presented. Models of each of the major ionic currents present in these cells are formulated and validated using experimental data obtained from studies of recombinant human ion channels and/or whole-cell recording from single myocytes isolated from human left-ventricular subepicardium. Continuous-time Markov chain models for the gating of the fast Na(+) current, transient outward current, rapid component of the delayed rectifier current,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
246
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(252 citation statements)
references
References 70 publications
4
246
0
2
Order By: Relevance
“…[8]). SNC is found, for example, in the Iyer-Mazhari-Winslow [9] or in the Drouhard-RobergeBeeler-Reuter (DRBR) model [10,11] employed in the study here, and it is often observed under conditions of low extracellular potassium concentration [12]. Recently, it has been shown to potentiate the onset of alternans in cultured cardiac cell strands [13] and also in generic models of spiral wave formation [14].…”
mentioning
confidence: 79%
“…[8]). SNC is found, for example, in the Iyer-Mazhari-Winslow [9] or in the Drouhard-RobergeBeeler-Reuter (DRBR) model [10,11] employed in the study here, and it is often observed under conditions of low extracellular potassium concentration [12]. Recently, it has been shown to potentiate the onset of alternans in cultured cardiac cell strands [13] and also in generic models of spiral wave formation [14].…”
mentioning
confidence: 79%
“…Cardiac electrophysiology models often do not include tension development, but given that peak tension is reached during the decay phase of the calcium transient and that calcium buffering will have the greatest effect during peak calcium, the static unbinding rate of calcium could be approximated as ~100s -1 . This is not easily compatible with the routinely used values of 19.6s -1 (Bondarenko et al 2004, Mahajan et al 2008, Shannon et al 2000, 40s -1 (Iyer et al 2004, Pandit et al 2001) and 200s -1 (Noble et al 1998). …”
Section: Models Of Cell Contractionmentioning
confidence: 85%
“…Specifically, motivated by knowledge of protein structure, Markov models can consist of a large number of states and transitions, which may be excessive from an information theoretical point of view. For example, the transient outward K + current I to has been modelled using ten-state Markov models for each of the two components (I Kv4.3 and I Kv1.4 ), leading to a total of 20 states to describe I to (Iyer et al 2004).…”
Section: Models For Ion Channelsmentioning
confidence: 99%
“…The past two decades have witnessed the development of increasingly sophisticated DEMs [9], which unravel in great detail the underlying cellular processes [17,22,24,14]. Such models are essential in the understanding of the intrinsic ionic mechanisms, and in the development of novel treatment strategies.…”
Section: Introductionmentioning
confidence: 99%